Analisis proksimat dan aktivitas antioksidan teh herbal daun tin (Ficus Carica L.) menggunakan metode DPPH (2,2-Diphenyl-1-picrylhidrazyl) - Rini Handayani; Cindi Nopita; Rina Kurniaty; Noni Zakiah (Poltekkes Kemenkes Aceh, 2024)
Background: Excess free radicals can cause degenerative diseases. Antioxidants are important compounds that counteract free radicals. Treatment with natural ingredients is considered safe and has relatively few side effects. plant that can counteract free radicals is the tin plant (Ficus Carica L.). The dried leaves of tin (Ficus Carica L.) can be used as herbal tea.Objectives: To determine the levels of proximate components and prove the antioxidant activity of Tin leaf herbal tea (Ficus Carica L.) using the DPPH (2,2-diphenyl-1-picrylhydrazil) method.Methods: This study used a laboratory experimental design. The research was conducted in the Department of Hebarium Biology FMIPA and Chemistry Laboratory FKIP Syiah University. Proximate content analysis included moisture, ash, and fiber content (gravimetry), protein content (Kjeldahl), fat content (Soxhletation), and carbohydrate content (by difference Antioxidant activity was determined using DPPH (2,2-diphenyl-1- picrylhydrazil) method on tin leaf herbal tea (Ficus Carica L.) with samples of 5 (five) concentrations of 2; 4; 6; 8; and 10 ppm. Data were analyzed by calculating the percent inhibition and determining the IC50 value..Results: The results of proximate analysis showed that tin leaf herbal tea (Ficus Carica L.) contained 559% water; 7,70% ash; 3,26% fat; 7,56% protein; 4,79% crude fiber; and 71,10% carbohydrate. Tin leaf herbal tea (Ficus Carica L.) is proven to have the ability to reduce free radicals with the DPPH method with very strong intensity, where theresulting IC50 is 7,21 ppm, where vitamin C as a comparison produces an IC50 value of 6,65 ppm which is categorized as very strong.Conclusion: Tin leaf herbal tea (Ficus Carica L.) tested using the DPPH method has antioxidant activity and the IC50 value of Tin leaf herbal tea of 7.21 ppm shows that the activity of Tin leaf herbal tea (Ficus carica L.) is categorized in a very strong category as an antioxidant.Keywordsantioxidant, tin leaves, herbal tea, DPPH, proximate